Examining the Influence of Organizational Change Management Strategies on Employee Resistance and Adaptation - Asrori, Ali (Penelitian dan Pengembangan Ilmu, 2024)
This research aims to explore the factors that influence employee adaptation to organizational change. Using a systematic literature review approach, we analyzed various individual factors and organizational strategies that have the potential to influence employee adaptation levels. The results of our analysis identified several key factors including age, education, personality, change strategy, quality of communication, social support, and level of ambiguity. Apart from that, this research also proposes a research framework that can be the basis for further research in understanding the dynamics of employee adaptation in the context of organizational change.